2021
DOI: 10.1111/papr.13027
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided L5/S1 intradiscal needle placement using biplanar approach with the patient in the lateral decubitus position: A report of three cases

Abstract: Background The use of ultrasound (US)‐guided intradiscal injection has been described in the literature with the patient lying in the prone position; however, many patients are unable to lie in the prone position. Therefore, we describe an innovative technique of US‐guided platelet‐rich plasma (PRP) administration in the lumbar intervertebral disc (IVD) of 3 patients with chronic lower back pain who failed to improve with conservative management. Case Series For all the 3 patients, magnetic resonance imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This presented technical challenges and posed a potential risk of nerve root injury. Lam et al reported a technique that approaches the disc more laterally compared to the earlier study [6]. However, their report was limited to injections in the intervertebral disc between the fifth lumbar vertebra and the sacrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presented technical challenges and posed a potential risk of nerve root injury. Lam et al reported a technique that approaches the disc more laterally compared to the earlier study [6]. However, their report was limited to injections in the intervertebral disc between the fifth lumbar vertebra and the sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…A study following a group of lumbar disc herniation cases over 13 years indicated that 14% of cases treated conservatively progressed to surgery, suggesting that intradiscal injections may be performed in at least an equivalent or greater proportion [4]. Intradiscal injections are typically performed under fluoroscopy, and reports of intradiscal injections under ultrasound guidance are extremely rare [5,6]. We report a case in which we performed a new method of intradiscal injection under ultrasound guidance for lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 96%
“…Usually, this procedure is performed under imaging guidance such as real‐time multiplanar fluoroscopy and computed tomography (CT), to improve the success rate and reduce adverse events. Recently, the use of ultrasound for guiding intradiscal injection has made this procedure more convenient, safer, and decreased the physical load and radiation exposure 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of ultrasound for guiding intradiscal injection has made this procedure more convenient, safer, and decreased the physical load and radiation exposure. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation